Juridical Review of the Zonation System in the Implementation of Minister of Education and Culture Regulation Number 44 of 2019 Regarding the 2020’s New Students Admission Related to the Law Number 20 of 2003 Regarding the National Sistem in the Justice - Mohammad Chusnul Yakin (LEGAL BRIEF, 2021)
This study aims to analyze the implementation of the zoning system according to Government Regulation Number 44 of 2019 concerning the Admission of New Students linked to the mandate of Law Number 20 of 2003 concerning the National Education System, and the impact of implementing the zoning system for the community from a justice perspective. This research is descriptive analytical with a normative juridical approach, and data collection techniques by conducting literature studies and interviews, then the data obtained is analyzed qualitatively juridical. The conclusions and results of the research: (1). The implementation of the zoning system according to Government Regulation Number 44 of 2019 concerning the Admission of New Students is linked to Law Number 20 of 2003 concerning the National Education System, the government only regulates the system that reviews mileage and the provisions of the system and procedures for its implementation without considering the problem of equitable development education and its facilities that have not been fully implemented means that the mandate of Law Number 20 of 2003 concerning the National Education System cannot yet be implemented with the existence of Permendikbud Number 44 of 2019 concerning the Admission of New Students with regard to the zoning system, (2) Implementation of the Zoning System for the Community Judging from Justice Perspective. The main principle of social justice is the basic structure of society, the structure of the main social institutions in a cooperation scheme. This principle regulates the granting of rights and obligations in institutions and determines the distribution of enjoyments and the burdens of social life. Thus, the zoning system has not fully provided a sense of justice apart from the adigums regarding the trend regarding paforit schools.